Reaksi Pasar Modal terhadap Fluktuasi Nilai Tukar Rupiah dan US Dollar di Sektor Perbankan - Rasyid, Syarifuddin; Darmawati, Darmawati; Tandilino, Charles; Irianto, Laode Bagus Wijaya (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This research aims to analyze the market reaction due to fluctuations in the exchange rate of the Rupiah and the US Dollar on the stock prices of the banking sector listed on the Indonesia Stock Exchange using the event study method through the indicators of Average Abnormal Return (AAR) and Average Volume Trading Activity (AVTA). The data collection technique is secondary data obtained from official sources, namely the Indonesia Stock Exchange (IDX) and Yahoo Finance. The population that became the study sample consists of 46 banking sector companies listed on the IDX, with an observation period of 15 trading days. Statistical testing was conducted using the SPSS statistical tool with a paired sample t-test. The results of the paired sample t-test showed that the significance value for AAR was 0.596 and for AVTA was 0.519 (p > 0.05), indicating no significant difference between the averages before and after the event. Additionally, descriptive analysis shows a stability pattern in both indicators, reflecting the market's response to the event without any significant spikes. These findings affirm that the banking sector has a high resilience to events of rupiah exchange rate fluctuations, making it a key pillar of the capital market that provides stability and liquidity to the financial system. This research recommends extending the observation period and exploring the impact of monetary policy to understand the dynamics of the relationship between exchange rate fluctuations and the performance of the financial sector.